Análise das exportações de amêndoas de castanha de caju pelas empresas beneficiadoras cearenses no período de 2007 A 2011 - Silva, Antonio César Pinheiro da (2014)
The sales of cashew nut from Ceará to the world represents around 70% of the market exports of almonds from Brazil and around 20% of what is consumed in the world. They are mainly exported to the US market. Given the great representability of the local market in national and international scenarios and the recent loss of market share due to the emergence of strong competitors, this work seek to estimate how the local producers of cashew nut react to determined variables group. We estimated one offer equation for the producing sector using the two stages least square (2SLS). Besides price and quantity, a group of control variables were collected, and when inserted in the estimated equation they can make some simultaneity with the sales destined to the foreign market. Knowing this, the two stages least square (2SLS) was the method chosen to eliminate identification problems and get estimations to correct possible remaining bias of simultaneity. This work evidences that the price did not show significance of 5%, possibly to be determined by the international market, and so, it is beyond the domain of the Ceará`s producers as this one acts as a price taker. It shows also that the coin rates, energy , the US crysis started in 2008 and the available US earnings represents 1% significance and signs awaited in the offer curve.